2000
DOI: 10.1074/jbc.m002916200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Determinants for the Specificity ofArabidopsis Thioredoxins h in Yeast Complementation

Abstract: The disruption of the two thioredoxin genes in Saccharomyces cerevisiae leads to a complex phenotype, including the inability to use methionine sulfoxide as sulfur source, modified cell cycle parameters, reduced H 2 O 2 tolerance, and inability to use sulfate as sulfur source. Expression of one of the multiple Arabidopsis thaliana thioredoxins h in this mutant complements only some aspects of the phenotype, depending on the expressed thioredoxin: AtTRX2 or AtTRX3 induce methionine sulfoxide assimilation and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 31 publications
(27 reference statements)
1
22
0
Order By: Relevance
“…The redox potential of these isoforms is similar to the WCGPC isoforms (around -285 mV) [25]. Nevertheless, yeast complementation experiments have shown that modification of AtTrxh3 active site (WCPPC to WCGPC) restores a partial sulfate assimilation phenotype [31]. Furthermore, mutation of the PtTrxh3 active site (WCGPC to WCPPC) strongly modifies the protein conformation [32].…”
Section: Physical and Mechanistic Aspects Of Thioredoxinmentioning
confidence: 97%
“…The redox potential of these isoforms is similar to the WCGPC isoforms (around -285 mV) [25]. Nevertheless, yeast complementation experiments have shown that modification of AtTrxh3 active site (WCPPC to WCGPC) restores a partial sulfate assimilation phenotype [31]. Furthermore, mutation of the PtTrxh3 active site (WCGPC to WCPPC) strongly modifies the protein conformation [32].…”
Section: Physical and Mechanistic Aspects Of Thioredoxinmentioning
confidence: 97%
“…In particular, both ATTRX3 and ATTRX5 contain the sequence WCPPC in their active sites rather than the much more common WCGPC, and some evidence suggests this difference is important for determining substrate specificity (Bré hé lin et al, 2000;Mazzurco et al, 2001). ATTRX3 and ATTRX5 are also the two most highly expressed Arabidopsis TRXhs based on EST abundance, and both are expressed in the vascular tissue of leaves .…”
Section: Discussionmentioning
confidence: 99%
“…The different methods consisting in an in vitro reduction by NTR/TRX systems followed with free thiol labeling are not specific either, due to the presence of endogenous TRX systems in the protein extracts. Several studies have shown, using complementation of a yeast TRX mutant strain by plant TRX genes, that Arabidopsis cytosolic and chloroplastic TRX isoforms exhibit distinct specificities in vivo (Mouaheb et al 1998;Bré hé lin et al 2000;IssakidisBourguet et al 2001). Thus, the recently developed yeast two-hybrid strain deficient for cytosolic thioredoxins appears as a promising tool to allow in vivo analysis of TRX-target specificity.…”
Section: Thioredoxinsmentioning
confidence: 97%